Livestock to promote rural income diversification and growth in Vietnam: finding appropriate policy options - Jabbar, M.A. (International Livestock Research Institute, 2000)
This study is conducted to contribute to the formulation of a strategy for the development of the livestock sector as a key element of rural development in Vietnam. It describes the structure of the livestock system including the key characteristics of the production and marketing system, the meat processing industry, the structure of trade, and the pattern of meat consumption; identifies the incentives and constraints to the development of a modern livestock system, including investment in and adoption of new breeds, use of high quality feed, availability and cost of veterinary services, upgrading of meat processing facilities, production of lean meat, and quality control; studies the determinants of livestock supply and feed demand in the context of a diversified agricultural system; studies the characteristics of meat demand in Vietnam, particularly in the context of urban areas; identifies the constraints and the opportunities of meat exports and the comparative advantage of meat production in Vietnam vis a vis other countries in Southeast and East Asia; identifies the barriers to entry of the poor and women into livestock production for the market and the policies and institutions that facilitate small and medium enterprises to expand their commercial operations; identifies and analyses alternative policy options for the development of the livestock sector and their impact on income and employment in rural areas; and enhances national capacity in policy analysis.